A Comparative Study of Somatic Development of Children Living at Rabka during Years 1965, 1972 and 1977 - Hałuszka, Janusz; Łęczyński, Janusz; Zaleszczuk, Andrzej (Anthropological Review, 1981)
In several hundred of children from the Primary School Nr 1 at Rabka. eight somatic characteristics were measured, first at the interval of seven years (1965-72) and then after five years (1977) repeated in a control study comprising 25% of children. Statistical characteristics of body dimensions are given in tables 1 and 2. It has been found that lengths of parts of the body increased considerably in groups of the same age examined at interval of seven years, further increase may be seen after next five years. Trunk length increased more than leg length suggesting that eventual influence of changed time of maturation is not a probable explanation of observed trend. The smallest differences in body length over observed time intervals occured in children of both sexes aged 10 years. Body weight and surface area changed in a way similar to body length. Chest circumference and its transversal diameter changed less regularly than lengths.Increase in body dimensions during a short period of time was in children from Rabka more pronounced than in other groups of Polish children examined by various authors. It may be concluded that besides supposed general causes of world-wide acceleration of physical development children living in Rabka were influenced by some local factors such as differentiated ethnic composition, social structure or compensation of unfavourable environmental factors. As a result children of Rabka who were in 1965 slightly under Polish standards, during 1970-s became at least equal in their somatic parameters to other Polish children.